Karakteristik Sensoris dan Fisikokimia Fruit Leather Buah Nanas Dengan Penambahan Kulit Mangga Sebagai Camilan Sehat - Hapsari, Martina Widhi; Rohana, Lina (Jurnal Ilmu Pangan dan Hasil Pertanian, 2024)
Fruit leather is a dried fruit product shaped into thin sheets. Pineapple and mango peel can be used as raw materials for fruit leather. Pineapple contains a high water content, making it perishable and shortening its shelf life. Meanwhile, mango peel, which has yet to be widely utilized, has the potential for addition due to its high pectin, fiber, and antioxidant content. This study aims to determine the formulation and the effect of adding mango peel on the moisture content, antioxidant activity, tensile strength, and elongation of fruit leather. The experimental design used was a Completely Randomized Design (CRD) with a ratio of pineapple to mango peel as follows: A0 = (100:0), A1 = (80:20), A2 = (70:30), A3 = (60:40), and A4 = (50:50). The data obtained were analyzed using ANOVA. If significant differences were found among treatments, further analysis was conducted using Duncan's Multiple Range Test (DMRT) at a 5% significance level. The best treatment selection was based on the overall results of organoleptic tests, followed by physicochemical analysis. The selected formula in this study was treatment A1 (80:20), with results showing a moisture content of 22.88%, antioxidant activity of 81.78%, crude fiber content of 19.66%, tensile strength of 6.43 MPa, and elongation of 10.3%.